Analysis of the Influence of Liquidity and Solvency on Profitability in Telecommunications Sub-Sector Service Companies Listed on the IDX in 2021-2024 - Ika Puspita Sari; Nurul Mazidah; Hafidza Nash’ul Amrina (Jurnal Pendidikan Edutama, 2026)
This study aims to find out how the effect of liquidity and solvency on profitability in service companies telecommunications sub-sector listed on the Indonesia Stock Exchange in 2021-2024. Variable in this study consists of Current Ratio (X1), Cash Ratio (X2), Debt to Assets Ratio (X3), Debt to Equity Ratio (X4), and Return on Asset (Y). Samples in this research is the 2021-2024 financial report. The sampling technique used is a saturated sampling technique. Data analysis techniques used is the classical assumption test and multiple linear regression. From the results of the analysis found that the variables Current Ratio, Cash Ratio, Debt to Asset Ratio have no effect significantly to profitability (Return on Asset). Variable Debt to Equity Ratio has a significant effect on profitability (Return on Asset). From this research, it can be suggested to creditors foe more considering the results of financial analysis, especially on the solvency ratio (Debt to Equity Ratio).